Pengendalian Hama Terpadu pada Peremajaan Sawit Rakyat di Kecamatan Pangkalan Kuras, Riau - Siti Rizkah Sagala; Hermanu Triwidodo; Widodo Widodo (Institut Pertanian Bogor, 2024)
The rapid development of oil palm replanting areas will lead to ecological problems such as plant disturbing organisms. Pest and disease attacks are obstacles farmers face when developing their farms, especially in smallholder oil palm plantations. This study aims to examine the components of cultivation techniques, environmental factors, and human resources that influence the application of IPM on smallholder oil palm replanting land in Pangkalan Kuras District, Pelalawan Regency, Riau Province. The methods used in this study included the purposive determination of 60 respondents, data collection through interviews with farmers, field surveys, and data analysis. The results showed that socio-economic aspects influenced farmers' actions in implementing IPM. Farmer knowledge about pests and diseases of oil palm plants was 36%. Farmers have applied several pest and disease control techniques in oil palm cultivation on replanting land. However, most farmers (60%) are still unfamiliar with the term IPM, need to learn the role of natural enemies in pest control in the field, and lack regular monitoring. Keywords: disease, IPM, palm oil, pest, replanting